Trade blocs - The World Bank; World Bank. (Oxford, England ; New York : Oxford University Press, 2000)
"The number of regional trade blocs has grown rapidly in recent decades. More than one-third of world trade now takes place within such blocs. New forms of bloc, encompassing both rich and poor countries, attempt to secure "deep integration" of economic activities. This book goes beyond existing studies to address the implications of these new forms of trading arrangement and to analyze the policy options that countries now face." "Trade Blocs analyzes both the political and the economic benefits of regional trade blocs. It argues that the benefits can sometimes be illusory and that careful economic choices have to be made if the schemes are to bring benefits. The trade-offs faced in these choices are analyzed, and the design of successful blocs is studied. The focus of the book is on policy choices for developing countries, with wider issues about the effect of the trade blocs on the world trading system also addressed."--BOOK JACKET.
Includes bibliographical references (p. 133-144).
Shakib
Keywords: Trade blocs; Regionalism; Commercial policy; International economic integration